THE ANALYSIS OF TRANSLATION PROCEDURES IN SUBTITLE OF â€œBOYCHOIRâ€ MOVIE - Syahrani, Nilda Iman; Tanduklangi, Amri; Muhsin, Muhammad Khusnun (Journal of Teaching of English, 2019)
The purposes of this study are to anlyze the translation procedure and the way of the translator in translating the subtitle of Boychoir movie. The scope of this study is focused on the type of translation procedures in translating the subtitle movie and also analyze the way of the translator in translating the subtitle on Newmark’s (1988:81) translation procedures which the procedures consist of 18 types. The methodology of this study was qualitative research. The researcher analyzed the data descriptively and presented the analysis result in the explanation form and supported by data presented in the form of table. In analyzing the data the procedures were as follows: juxtaposing both of English and Indonesian version, identifying, analyzing and classifying, and calculating the total numbers. The translation procedures found in the subtitle of the movie were literal translation, transference, naturalisation, cultural equivalent, functional equivalent, synonymy, transpositions, modulation, reduction and expansion, couplets. Keywords: Translation, Translation procedure, Subtitle, Boychoir movie